The miR166–mRNA network regulates vascular tissue differentiation in Moso bamboo - Li, Ying; Zhang, Shuqin; Zhang, Deqiang; Li, Xueping; Gao, Zhimin; Jiang, Zehui (Frontiers in Genetics, 2022)
miR166s play an important role in plant tissue differentiation. However, the functions of miR166s in the differentiation of vascular tissue in bamboo have not yet been elucidated. Here, we showed that five miR166s are overexpressed (tags per million reads > 2,000) in underground shoot samples of wild-type (WT) Moso bamboo (Phyllostachys edulis) and a thick-walled variant (P. edulis “Pachyloen”) throughout the developmental process. Potential targets of these miR166s include some genes encoding homeodomain-leucine zipper (HD-ZIP) transcription factors and protein kinases. Cleavage sites for miR166s were identified in seven PeHD-ZIP homologs and a protein kinase gene via degradome sequencing (p < 0.05). Dual-luciferase and transient expression assays confirmed the binding of miR166s to PeHOXs. Fluorescence in situ hybridization revealed that miR166s were localized to the xylem of the leaf, root, and internode of 2-month-old pot seedlings of WT Moso bamboo. Overall, these findings reveal that miR166s are regulators of vascular tissue differentiation in bamboo. The miR166s identified in our study provide novel targets for bamboo breeding.